2021
DOI: 10.3390/jcm10132748
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Changes in Kidney Transplant: Diagnostic Efficacy of miR-150-5p as Potential Rejection Biomarker, Pilot Study

Abstract: Background: The kidney allograft biopsy is considered the gold standard for rejection diagnosis but is invasive and could be indeterminate. Several publications point to the role of miRNA expression in suggesting its involvement in the acceptance or rejection of organ transplantation. This study aimed to analyze microRNAs involved in the differentiation and activation of B and T lymphocytes from kidney transplant (KT) patients’ peripheral blood leukocytes to be used as biomarkers of acute renal rejection (AR).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
0
21
0
Order By: Relevance
“…In transplant patients, immune suppression status is especially important for preventing graft rejections. This could explain why female patients with a worse long-term graft function have shown a significantly lower expression of miR-150 in our study [ 9 ].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In transplant patients, immune suppression status is especially important for preventing graft rejections. This could explain why female patients with a worse long-term graft function have shown a significantly lower expression of miR-150 in our study [ 9 ].…”
Section: Discussionmentioning
confidence: 88%
“…MiRNAs are groups of non-coding RNAs possessing essential cellular functions such as cell proliferation, cell differentiation, organ development and immuno-regulation [ 7 ]. Their various functions make them ideal non-invasive markers during certain evaluations or follow ups [ 8 , 9 ]. Renal graft biopsies are the current gold standard for the examination of entities involving renal graft dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…The Kruskal Wallis test and Dunn’s post hoc test with Bonferroni correction for multiple comparisons compared three or more groups. Correlation analyzes were carried out using the Spearman index, as previously published ( 5 , 21 , 22 ). For the longitudinal comparison of two related groups, the Wilcoxon non-parametric test for related samples was used.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, another study using logistic regression analysis showed that urinary miR-155-5p could identify patients with potential high risk of rejection at early stage of post-transplantation (95). Alfaro et al showed that miR-150-5p was decreased in acute rejection kidney transplantation patients, the decrease could be related to activation and proliferation of the immune system's cells (96). A pilot study showed that in the first 3 months post transplantation with tacrolimus therapy, urinary exosome derived miR-155-5p and miR-223-3p correlated with tacrolimus dose, miR-223-3p with serum creatinine, and miR-223-3p and miR-1228-3p with blood leukocytes, indicating that differentially expressed urinary exosome miRNAs might monitor tacrolimus therapy and renal graft function (97).…”
Section: Acute T Cell-mediated Rejection and Acute Antibody-mediated ...mentioning
confidence: 96%